(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Leaf, flower and seed coat extract of Peltophorumpterocarpum (DC.) K.Heyne. family CAESALPINIACEAE was found to havecertaintherapeutical valueswhich may usedto treat stomatitis, insomnia, skin problems, constipation and ring worm also itis known to be a good sleep inducer, bark is used for dysentery. In vitro antibacterial and anti fungal screening of total methanolic extract of Peltophorumpterocarpum (DC.) K.Heyne..Against bacteria and fungal by standard well plate method used for determining antibacterial and antifungal activity. The crude extract was dissolved in the solvents to obtain 40mg/ml, 10mg/ml of dilutions. The antimicrobial activities were determined by measuring the diameter of the inhibitory zones in mm using a zone reader. It shows moderate antibacterial and not any antifungal activity, Peltophorumpterocarpum (DC.)K.Heyne. can be used as antibacterial activities.